Los créditos de las cajas municipales y su relación con el producto bruto interno en la Región Loreto 2007-2022 - Arevalo Tuisima, Carlos Ewing (2024)
The present investigation addressed the effectiveness of the credits granted by the Municipal Banks in promoting economic growth, identifying existing problems and proposing recommendations to improve production in the Loreto region. The objective is to contribute to the design of policies and strategies that promote equitable access to financing and strengthen the contribution of the microfinance sector to the sustainable development of the region. To achieve this, the existing literature on the topic was reviewed, considering the economic and financial implications of our findings. In this sense, 64 quarterly observations were analyzed during the period 2007-2022, which cover the production value of the different economic activities and the aggregate amount of direct credits granted by the Municipal Banks in Loreto. As a result of this analysis, it was concluded that there is a very strong positive relationship of 91.42% between the variables. So, when the direct credits granted by the Municipal Banks increase by S/ 1 thousand, the value of GDP increases by S/ 5,123, thus evidencing the multiplier effect of credits in Loreto.